Access to Justice and Fair for the Poor: How Effective the Legal Aid Provided by Government? - Dani Setiawan (The Indonesian Journal of International Clinical Legal Education, 2021)
Providing legal assistance to the poor continues by the government to realize legal access and justice for all levels of society. Several regulations regarding legal aid have been issued by the state through the law and implementing regulations, but the fact is that the provision of legal aid is not yet effective. This causes a lack of access to law and justice for the poor. The effectiveness of providing legal aid by the government needs to be assessed to see how effective the legal aid program provided by the government is to realize legal access and justice for the poor. Therefore, criticism and advice should be given to the government in order to optimize legal assistance in order to achieve legal access and justice for all levels of society.